CONSUMER CONFIDENCE IN HALAL SKIN CARE PRODUCTS IN ISLAMIC ECONOMICS - Fatonah, Nurul Fitriani; Diana, Dessy Rahmawati; Gunariah, Frilla; Nurdiansyah, Irdan; Syamjani, Raaf (KOMITMEN: Jurnal Ilmiah Manajemen, 2025)
This study aims to analyze consumer trust in halal skincare products within the framework of Islamic economics. In recent years, the demand for halal skincare products has increased alongside the growing awareness among Muslim consumers about the importance of product compliance with Sharia principles. Consumer trust plays a crucial role in purchase decisions. In the Islamic context, the halal label encompasses not only the ingredients used but also the production processes that adhere to Sharia guidelines. This study employs a quantitative approach using a questionnaire distributed to 59 respondents who use halal skincare. Data analysis was conducted using simple linear regression to determine the influence of consumer trust on the quality of halal skincare products within Islamic economics. The results show that consumer trust significantly affects the purchase of reliable halal skincare products, with halal certification serving as a key factor in providing safety and confidence for Muslim consumers in choosing skincare products.